Intergrated leachate treatment by sequencing batch reactor (SBR) and micro-zeolite (MZ) - Abu Bakar, Amnani (2015)
Biological treatment has a lot of potential in leachate treatment with the ability of the biodegradable substrates and this method can reduce the cost of treatment residues with respect to ecological and economical requirements.The aims of this study are to investigate the effect of biological treatment by using sequencing batch reactor (SBR) system in different condition consisting anaerobic (An), anoxic (Ax), and oxic (Ox) with different reaction time. An integration in combining phases consisting An/Ax/Ox is used in order to achieve maximum removal. Then, followed by the performance of combination phases consisting An/Ax/Ox in SBR system with addition of adsorption adsorbent micro-zeolite (MZ) (size range 75-150 μm) at different dosages. The raw leachate and sludge were collected from sanitary landfill from Tanjung Langsat, Pasir Gudang. An condition has better performance in an SBR system at optimum reaction time 11 hr promoting the percentage removal efficiency of chemical oxygen demand (COD), ammonia nitrogen (AN), total nitrogen (TN), total phosphorus (TP) and suspended solid (SS) and turbidity which were 77%, 74.65%, 75.07%, 76.05%, 63.91%, and 62.67% respectively. The result indicated that the combined condition consisting An/Ax/Ox at the optimum time reaction of each condition gives the removal efficiency COD, AN, TN, TP, SS, and turbidity which were 85.78%, 88.65%, 87.07%, 86.9%, 81.92% and 81.15% respectively. The application addition of adsorption adsorbent gives optimum dosage at 5 g/L. The addition of MZ shows good removal efficiency which were more than 90% at overall parameter.